Use of Chitosan from Southern King Crab to Develop Films Functionalized with RGD Peptides for Potential Tissue Engineering Applications - Forero, Juan Carlos; Carvajal, Karina; Guzmán, Fanny; Acevedo, Cristian; Osses, Nelson; Santana, Paula (My University, 2023)
Southern King Crab (SKC) represents an important fishery resource that has the potential to be a natural source of chitosan (CS) production. In tissue engineering, CS is very useful to generate biomaterials. However, CS has a lack of signaling molecules that facilitate cell–substrate interaction. Therefore, RGD (arginine–glycine–aspartic acid) peptides corresponding to the main integrin recognition site in extracellular matrix proteins have been used to improve the CS surface. The aim of this study was to evaluate in vitro cell adhesion and proliferation of CS films synthesized from SKC shell wastes functionalized with RGD peptides. The FTIR spectrum of CS isolated from SKC shells (SKC-CS) was comparable to commercial CS. Thermal properties of films showed similar endothermic peaks at 53.4 and 53.0 °C in commercial CS and SKC-CS, respectively. The purification and molecular masses of the synthesized RGD peptides were confirmed using HPLC and ESI-MS mass spectrometry, respectively. Mouse embryonic fibroblast cells showed higher adhesion on SKC-CS (1% w/v) film when it was functionalized with linear RGD peptides. In contrast, a cyclic RGD peptide showed similar adhesion to control peptide (RDG), but the highest cell proliferation was after 48 h of culture. This study shows that functionalization of SKC-CS films with linear or cyclic RGD peptides are useful to improve effects on cell adhesion or cell proliferation. Furthermore, our work contributes to knowledge of a new source of CS to synthesize constructs for tissue engineering applications.
Keywords: Crab shell waste; Chitosan; Films; RGD peptides; Tissue engineering; Cell adhesion